WHAT MADE IMPLEMENTING EFFECTIVE ELEARNING HARD?: A SYSTEMATIC LITERATURE REVIEW - Satria, Deki (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
Covid-19 pandemic change a lot of industries in the world, including education. Education industries have become the third most affected by the pandemic and force educational institutions to change how they deliver their education services. eLearning became one of the solutions to these problems. But the implementation of eLearning proved to be hard and faced many obstacles or barriers. This paper is a Systematic Literature Review paper using Kitchenham. The systematic review results show that there were four categories of barriers in elearning: human factors, technological factors, financial factors, and organizational factors. To tackle this problem, educational institutions need to change the way they deliver the material; one way to change it is by gamification. The organization also has a vital contribution to tackle these barriers as the policymakers and supporters, both financially and as training providers.